Faktor-Faktor Yang Mempengaruhi Kualitas Audit Pada BPK RI Perwakilan Kalimantan Timur - Nindia Tyasing Kusuma Wardani; Hj. Nurita Affan; Dhina Mustika Sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
ABSTRACTThis research was aimed to examine empirically the effect of audit independence, level of education and audit experience on audit quality of Badan Pemeriksa Keuangan Republik Indonesia representative of Kalimantan Timur province. Supervised by Hj. Nurita Affan and Dhina Mustika Sari.            The sample is auditor’s of Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Kalimantan Timur. The sample was conducted by saturated sample method. The collecting data was conducted by 45 exemplar. Statistic metode by PLS-SEM (Partial Least Square-Structural Equation Modelling) and assist by SmartPLS aplication.             The research showed that there was a significant effect of audit experience upon audit quality and insignificant effect of audit independence and level of education upon audit quality. Value of the coefficient of determination indicates the independency, level of education and audit experience that together effect to audit quality of 66,7% while the remaining 33,3% are influenced by other outside factor model.